Epidemiological and clinical profile of patients with pressure injury after spinal cord trauma (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Introduction: The prevalence of pressure injury (PI) varies with the clinical environment and the characteristics of the patient, thus, patients with spinal cord trauma (SCT) are configured among those with greater predisposition to the length of hospitalization, presenting impaired movements and sensitivity. Objective: To know and analyze the prevalence of pressure injury in patients suffering from spinal cord trauma hospitalized in a reference hospital. Method: Cross-sectional, retrospective study. The sample consists of medical records of patients with spinal cord trauma who presented pressure injury during hospitalization in a reference hospital in the state of Pará, Brazil, during the period from 2013 to 2016. Results: We analyzed 565 medical records of patients with spinal cord, with the prevalence of PI in of 8% of patients with SCT. The mean age was 37 years, with 80% composed of men, with an average length of hospitalization of 66.68 days. The majority presented as etiology of spinal cord injury accidents by firearm and fall, with 32 and 30% respectively. Spinal cord injury was predominant in the thoracic region (50%), where 64% had paraplegia as sequelae and 86% presented pressure injury in the sacral region. Conclusion: It was possible to identify the prevalence of PI in patients with SCT and to know its behavior. Thus, the availability of data helped to demonstrate the occurrence of PI as a complication in patients with SCT during hospitalization, and can serve as a basis for the allocation of preventive resources and measures, as well as further studies on the theme.